2006
DOI: 10.1158/1055-9965.epi-05-0914
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Screening among Women in Metropolitan Areas of the United States by Individual-Level and Area-Based Measures of Socioeconomic Status, 2000 to 2002

Abstract: Background: Few studies have examined cancer screening among women residing in metropolitan areas in relation to both individual-level and area-based measures of socioeconomic status (SES). To learn more, we examined selfreported rates of Papanicolaou (Pap) testing among women living in metropolitan areas in relation to individual-level measures of SES (household income and education), and area-based measures of SES (percentage of residents living in poverty, percentage with low education, and percentage worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
73
2
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 22 publications
15
73
2
3
Order By: Relevance
“…In accordance with the existing literature, education, income, having health insurance, and having a PHP were found to be significant predictors of adequate cervical cancer screening behavior 11,[15][16][17] ; age, education, income, having health insurance, and having a PHP were found to be significant predictors of adequate breast cancer screening behavior. 11,18,19 Overall, our findings from analyses of the 2004 national BRFSS sample provide strong evidence to support that having a PHP and health insurance are 2 important independent factors associated with adequate cervical and breast cancer screening.…”
Section: Discussionsupporting
confidence: 87%
“…In accordance with the existing literature, education, income, having health insurance, and having a PHP were found to be significant predictors of adequate cervical cancer screening behavior 11,[15][16][17] ; age, education, income, having health insurance, and having a PHP were found to be significant predictors of adequate breast cancer screening behavior. 11,18,19 Overall, our findings from analyses of the 2004 national BRFSS sample provide strong evidence to support that having a PHP and health insurance are 2 important independent factors associated with adequate cervical and breast cancer screening.…”
Section: Discussionsupporting
confidence: 87%
“…4 Barriers to screening for socioeconomically disadvantaged women include not being able to afford transportation or child care, lack of awareness of the need for screening, low health literacy and, again, lack of physician recommendation. 29,30,[43][44][45] Our results are consistent with other Canadian and international literature. A recent multi-country study showed that disability was consistently more prevalent in the poorest than richest quintiles.…”
Section: Cmaj Opensupporting
confidence: 91%
“…[7,28] Despite the fact that all study participants were eligible for IHS-funded health care, markers for socioeconomic status (education and income) predicted improved screening rates. Studies in many other populations have found educational status and/or income to be predictive of cancer screening [5,8,[29][30][31][32][33][34]. The finding has important implications for reaching American Indian and Alaska Native people to improve cancer screening.…”
Section: Discussionmentioning
confidence: 99%